Studi Skema Konfigurasi PLTS (Studi Kasus: Pulau Kaledupa, Sulawesi Tenggara) - Parapa, Hendra Budiono Putra (Jurnal Teknologi Elekterika, 2022)
PLTS as one of the most promising technologies to produce economical, clean and sustainable electrical energy can currently increase the national energy mix because of its nature that can be easily built and its development requires a short time compared to other technologies. The purpose of this research is to study the PV mini-grid configuration scheme in the islands. The case study used in this research is on Kaledupa Island, Southeast Sulawesi. The data used is the actual data on the electrical load on the island of Kaledupa and data on the potential for solar radiation sourced from solarglobalatlas.info. Actual electrical load data and solar radiation potential data are processed using an excel application to calculate the PLTS capacity and energy storage system, then a capacity sizing analysis is carried out from the calculation results. This study concludes that the PV, Energy Storage System and Diesel configuration scheme is the most likely scheme to be applied to the electricity system on the island of Kaledupa, taking into account the load conditions in the electrical system